CGIAR Capacity Development Framework : Engaging with Partners - Dror, Iddo (International Livestock Research Institute, 2014)
Presented by Iddo Dror, Head of Capacity Development, International Livestock Research Institute (ILRI) Chair, CGIAR Capacity Development Community of Practice at Celebrate FARA, Johannesburg, 27 Nov 2014